2019
DOI: 10.1111/ibi.12785
|View full text |Cite
|
Sign up to set email alerts
|

Using microphone arrays to investigate microhabitat selection by declining breeding birds

Abstract: Understanding the microhabitat preferences of animals can help managers to develop better conservation and recovery strategies, but is challenging. Traditional methods are limited by cost, accuracy, and human resources. In this study, we investigated avian microhabitat preferences using microphone arrays that are capable of accurately localizing vocalizing birds. Our objective was to identify the microhabitat associations of two common species in steep population decline, the Boreal Chickadee Poecile hudsonicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Six studies calculated animal abundance, either by direct calculation of number of individuals (Frommolt & Tauchert, 2014; Hedley, Huang, & Yao, 2017; Spillmann et al, Willems, van Noordwijk, Setia, & van Schaik, 2017; Wahlberg et al, 2003; Wilson & Bayne, 2018) or indirectly by calibration of acoustic indices, as described by Stevenson et al (2015) (Thompson et al, 2009). Five studies used localization to infer territory boundaries or habitat use, including assessing animals' relationships with anthropogenic or natural habitat features (Ethier & Wilson, 2019; Hennigar, Ethier, & Wilson, 2019; Kershenbaum et al, 2019; Spillmann et al, 2017; Wilson & Bayne, 2018). Three studies separated animal sounds from background noise to improve species classification (Kojima, Sugiyama, Hoshiba, Suzuki, & Nakadai, 2017; Kojima, Sugiyama, Suzuki, Nakadai, & Taylor, 2016; Suzuki, Matsubayashi, Nakadai, & Okuno, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies calculated animal abundance, either by direct calculation of number of individuals (Frommolt & Tauchert, 2014; Hedley, Huang, & Yao, 2017; Spillmann et al, Willems, van Noordwijk, Setia, & van Schaik, 2017; Wahlberg et al, 2003; Wilson & Bayne, 2018) or indirectly by calibration of acoustic indices, as described by Stevenson et al (2015) (Thompson et al, 2009). Five studies used localization to infer territory boundaries or habitat use, including assessing animals' relationships with anthropogenic or natural habitat features (Ethier & Wilson, 2019; Hennigar, Ethier, & Wilson, 2019; Kershenbaum et al, 2019; Spillmann et al, 2017; Wilson & Bayne, 2018). Three studies separated animal sounds from background noise to improve species classification (Kojima, Sugiyama, Hoshiba, Suzuki, & Nakadai, 2017; Kojima, Sugiyama, Suzuki, Nakadai, & Taylor, 2016; Suzuki, Matsubayashi, Nakadai, & Okuno, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Field deployment typically requires multiple people and can be time‐consuming, especially at larger scales and with many ARUs. Ethier and Wilson (2019) reported that two people required 1–2 hr to deploy four GPS‐synchronized ARUs that were separated by 40 m.…”
Section: Resultsmentioning
confidence: 99%
“…Their locations were selected at random, but with the constraints that they were within 1 km of road or trail access, at least 500 m apart from each other, and not in a swamp, bog or body of water. The microphone arrays were also used in other projects investigating the relationships among habitat characteristics, anthropogenic disturbance, avian community composition and avian behaviour (Ethier and Wilson , Hennigar et al ). One of those studies involved broadcasting experimental noise or light, but those manipulations were only conducted at a given location after the data for the current study had been collected (Hennigar et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This second step was repeated 100 times, with each iteration using a finer‐resolution lattice and a smaller study area (equal to the spatial resolution of the previous iteration) centred on the estimated origin of the song from the previous iteration. (Wilson et al , Ethier and Wilson , Hennigar et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation